Vulnerability Factors, Adjustment, and Opioid Misuse in Chronic Non-Cancer Pain Individuals. - Ramírez-Maestre, María del Carmen; Barrado-Moreno, Victoria; Esteve-Zarazaga, Rosa; Serrano-Ibáñez, Elena Rocío; De la Vega, Rocío; Ruiz-Párraga, Gema Teresa; Fernández Baena, Mariano; Jensen, Mark P.; López-Martínez, Alicia Eva (Elsevier, 2024)
There are several person variables that pre-date injury or pain onset that increase the probability of maladjustment to pain and opioid misuse. The aim of this study was to evaluate the role of two diathesis variables (impulsiveness and anxiety sensitivity) in the adjustment of individuals with chronic noncancer pain and in the opioid misuse. The sample comprised 187 individuals with chronic noncancer pain. The hypothetical model was tested using correlation and structural equation modelling analyses. The results show a significant association between impulsiveness and anxiety sensitivity and all the maladjustment variables, and between impulsiveness and anxiety sensitivity and opioid misuse and craving. However, although the correlation analysis showed a significant association between adjustment to pain and opioid misuse, the SEM analysis showed a nonsignificant association between them (as latent variables). The findings support the hypothesis that both impulsiveness and anxiety sensitivity are vulnerability factors for maladaptive adjustment to chronic pain and opioid misuse.
Keywords: Dolor crónico; Opiáceos - Uso terapéutico; Medicamentos - Abuso; Dolor - Aspectos psicológicos; Chronic pain; Impulsiveness; Anxiety sensitivity; Pain adjustment; Opioid misuse; Craving